HUMAN RIGHTS AND LEGAL PROTECTION FOR VICTIMS OF RAPE IN INDONESIA'S LEGAL FRAMEWORK - Siti Syahida Nurani (Khairun Law Journal, 2021)
The issue of Human Rights (HAM) is becoming an increasingly important agenda, the international community continues to urge all member states of the United Nations to take various steps and actions, including making laws to eliminate discrimination and violence against women. Indonesia's policy to ratify the global law mentioned above, is suspected by the rampant problems of violence faced by almost every nation and country on this earth.Â  The research methodology used is library research which is carried out by searching, taking an inventory and studying laws and regulations, doctrines, and other secondary data, which are related to the focus of the problem. in the legal framework Indonesia has provided guarantees for human rights (both women and men) as stated in the second amendment of the 1945 Constitution of Article 28 A-J and Law No. 39 of 1999 on Human Rights. UU no. 7 of 1984 concerning the Elimination of Discrimination Against Women or the Ratification of the Women's Convention, which states that the state will make maximum efforts to eliminate all forms of discrimination against women, including violence against women, in particular sexual violence is regulated in the Child Protection Law and the Criminal Code, while other forms of protection for victims of sexual crimes.